Development of a new real time responding hydrogen fueling protocol. (29th May 2020) - Chae, Chung Keun; Park, Byung Heung; Huh, Yun Sil; Kang, Seung Kyu; Kang, Su Youn; Kim, Han Na
Abstract: Current Hydrogen Fueling Protocols (HFPs), such as SAE J2601, have been developed for non-communication and communication. They have problems due to the lack of versatility in their scope of application and the efficiency of their application method. The purpose of this study is to develop a new HFP for communication using a Real Time Responding method with outstanding efficiency and versatility. The new HFP was developed using simple model, that played the role of the engine of HFP, and a rigorous model that played the role as the testbed. This new HFP is founded to be more versatile and efficient compared to the existing HFP and to have excellent convenience, stability, safety, and economic feasibility. It is concluded that the new HFP can perform the function for communication only, while the existing HFP is used for both communication and non-communication. Highlights: Real time responding hydrogen fueling protocol with communication only. Shortening the fueling time of fuel cell vehicles with new fueling protocol. New hydrogen fueling protocol that need no look-up tables and no scope limits. Thermodynamic models for development of new hydrogen fueling protocol. Hydrogen fueling protocol operated by real-time simulation with real-time data.